Upregulation of elastase proteins results in aortic dilatation in mucopolysaccharidosis I mice - Ma, Xiucui (2008)
Mucopolysaccharidosis I (MPS I), known as Hurler syndrome in the severe form, is a lysosomal storage disease due to α-l-iduronidase (IDUA) deficiency. It results in fragmentation of elastin fibers in the aorta and heart valves via mechanisms that are unclear, but may result from the accumulation of the glycosaminoglycans heparan and dermatan sulfate. Elastin fragmentation causes aortic dilatation and valvular insufficiency, which can result in cardiovascular disease. The pathophysiology of aortic disease was evaluated in MPS I mice. MPS I mice have normal elastic fiber structure and aortic compliance at early ages, which suggests that elastin assembly is normal. Elastin fragmentation and aortic dilatation are severe at 6 months, which is temporally associated with marked increases in mRNA and enzyme activity for two elastin-degrading proteins, matrix metalloproteinase-12 (MMP-12) and cathepsin S. Upregulation of these genes likely involves activation of STAT proteins, which may be induced by structural stress to smooth muscle cells from accumulation of glycosaminoglycans in lysosomes. Neonatal intravenous injection of a retroviral vector normalized MMP-12 and cathepsin S mRNA levels and prevented aortic disease. We conclude that aortic dilatation in MPS I mice is likely due to degradation of elastin by MMP-12 and/or cathepsin S. This aspect of disease might be ameliorated by inhibition of the signal transduction pathways that upregulate expression of elastase proteins, or by inhibition of elastase activity. This could result in a treatment for patients with MPS I, and might reduce aortic aneurism formation in other disorders.